A randomized phase II study of ganetespib, a heat shock protein 90 inhibitor, in combination with docetaxel in second-line therapy of advanced non-small cell lung cancer (GALAXY-1) - Ramalingam, Suresh; Schmid-Bindert, Gerald (Annals of oncology, 2015)
Background: This trial was designed to evaluate the activity and safety of ganetespib in combination with docetaxel in advanced non-small cell lung cancer (NSCLC) and to identify patient populations most likely to benefit from the combination. Patients and methods: Patients with one prior systemic therapy for advanced disease were eligible. Docetaxel (75 mg/m2 on day 1) was administered alone or with ganetespib (150 mg/m2 on days 1 and 15) every 3 weeks. The primary end points were progression-free survival (PFS) in two subgroups of the adenocarcinoma population: patients with elevated lactate dehydrogenase (eLDH) and mutated KRAS (mKRAS). Results: Of 385 patients enrolled, 381 were treated. Early in the trial, increased hemoptysis and lack of efficacy were observed in nonadenocarcinoma patients (n = 71); therefore, only patients with adenocarcinoma histology were subsequently enrolled. Neutropenia was the most common grade ≥3 adverse event: 41% in the combination arm versus 42% in docetaxel alone. There was no improvement in PFS for the combination arm in the eLDH (N = 114, adjusted hazard ratio (HR) = 0.77, P = 0.1134) or mKRAS (N = 89, adjusted HR = 1.11, P = 0.3384) subgroups. In the intent-to-treat adenocarcinoma population, there was a trend in favor of the combination, with PFS (N = 253, adjusted HR = 0.82, P = 0.0784) and overall survival (OS) (adjusted HR = 0.84, P = 0.1139). Exploratory analyses showed significant benefit of the ganetespib combination in the prespecified subgroup of adenocarcinoma patients diagnosed with advanced disease >6 months before study entry (N = 177): PFS (adjusted HR = 0.74, P = 0.0417); OS (adjusted HR = 0.69, P = 0.0191). Conclusion: Advanced lung adenocarcinoma patients treated with ganetespib in combination with docetaxel had an acceptable safety profile. While the study's primary end points were not met, significant prolongation of PFS and OS was observed in patients >6 months from diagnosis of advanced disease, a subgroup chosen as the target population for the phase III study.